Bridging the Competence of Preparing Reputable Scientific Articles for Lecturers in the Field of Sharia Economics through Mastering Artificial Intelligence at the Ibrahimy Institute of Islamic Religion Genteng, Banyuwangi - Suprayitno, Eko; Meldona, Meldona; Asnawi, Nur; Djalaluddin, Ahmad; Oria, Ehsanullah (Asian Journal of Community Services, 2024)
Along with technological advances, Artificial Intelligence (AI) can be used to improve the quality and efficiency of the scientific article preparation process. Assistance in the preparation of reputable scientific articles for lecturers at the Ibrahimy Islamic Religious Institute, Genteng, Banyuwangi, was attended by 52 people with material covering the structure of scientific articles, the choice of reputable journals, the use of AI, and its ethical aspects. The mentoring methods are discussions and practices using AI platforms, namely Eskritor, Research Rabbit, and Mendeley. The success of the implementation of mentoring was measured through evaluations that showed an increase in participants' understanding, as well as positive feedback on AI skills.